Method for regenerating phosphorus iron slag into carbon-coated ferrous phosphide and application thereof

CN122916070APending Publication Date: 2026-10-16WELNENG ENVIRONMENTAL TECH (SUZHOU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611257441.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-19
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0002]由于锂离子电池具有一定的使用寿命,使得大量废旧锂离子电池需要经过在一段使用时间后进行回收处理,磷酸铁锂电池的废旧材料中含有锂、铁、磷等有价金属元素,目前对于废旧磷酸铁锂电池的回收处理,主要集中在锂的回收利用,对于磷铁渣的处理往往缺乏有效的方法,在对磷铁渣的处理过程存在生成的磷酸铁纯度较低、适用性差等问题

Benefits of technology

通过上对预处理后的磷铁渣进行筛选,以得到粒径满足≥200目的磷铁渣粉末,将磷铁渣粉末与第一酸溶液混合并加热反应,向反应后物质中添加铁源得到铁磷混合物,其中铁磷混合物为活化磷铁渣粉末,并控制所述铁磷混合物的铁磷比满足(1.75~2.1):1;配铁磷混合物与氨基酸盐、碳源溶解于溶剂并反应得到磷化亚铁前驱体,磷化亚铁前驱体为氨基酸功能化碳层负载的磷化亚铁前驱体,控制磷化亚铁前驱体在还原气体氛围下,经加热反应得到碳包覆磷化亚铁。本申请通过严格控制回收处理过程中的铁磷比,以制备得到纯度较高的、并且可作为电池级别应用的氨基酸功能化碳层负载磷化亚铁,同时整个工艺过程中采用了低能耗的回流加热处理和短时间的高温烧结,减少了能耗以此确保资源的合理利用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916070A_ABST
    Figure CN122916070A_ABST
Patent Text Reader

Abstract

The application discloses a method for regenerating phosphorus-iron slag into carbon-coated ferrous phosphide and application, relates to the recycling technical field of lithium battery materials, and comprises the following steps: pretreating phosphorus-iron slag, screening to obtain phosphorus-iron slag powder with a particle size meeting the purpose of greater than or equal to 200, mixing the phosphorus-iron slag powder with a first acid solution and heating to react, adding an iron source to the reaction substance to obtain an iron-phosphorus mixture, and controlling the iron-phosphorus ratio of the iron-phosphorus mixture to meet (1.75-2.1):1; dissolving the iron-phosphorus mixture, an amino acid salt and a carbon source in a solvent and reacting to obtain a ferrous phosphide precursor, and controlling the ferrous phosphide precursor to be heated to react in a reducing gas atmosphere to obtain carbon-coated ferrous phosphide. The application strictly controls the iron-phosphorus ratio in the recycling process to prepare the amino acid functionalized carbon layer loaded ferrous phosphide with high purity and capable of being applied to battery grade, and the whole recycling process reduces energy consumption and realizes the rational utilization of resources.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery material recycling technology, specifically to a method and application for regenerating ferrophosphide slag into carbon-coated ferrous phosphide. Background Technology

[0002] Because lithium-ion batteries have a limited lifespan, a large number of used lithium-ion batteries need to be recycled after a period of use. The waste materials of lithium iron phosphate batteries contain valuable metal elements such as lithium, iron, and phosphorus. At present, the recycling and processing of waste lithium iron phosphate batteries mainly focuses on the recycling and utilization of lithium. There is often a lack of effective methods for the treatment of phosphorus iron slag. In the process of treating phosphorus iron slag, there are problems such as low purity of the generated iron phosphate and poor applicability.

[0003] In some related technologies, the recycling and reuse of ferrophosphate slag mainly involves the reprocessing of iron phosphate, sodium ferric pyrophosphate and other sodium battery materials, or its conversion into iron and phosphorus sources. However, the recovered iron and phosphorus sources suffer from low purity and poor applicability, making them difficult to apply at the battery level. Furthermore, current ferrophosphate slag recycling processes suffer from low impurity removal efficiency and incomplete impurity separation, also resulting in low purity of the recovered products. In addition, the resource utilization rate of wastewater and impurities generated during the ferrophosphate slag treatment process is low, lacking an effective recycling and regeneration mechanism. Summary of the Invention

[0004] To address at least one of the problems mentioned in the background art, this application provides a method and application for regenerating ferric phosphate slag into carbon-coated ferrous phosphate. By recycling ferric phosphate slag from waste batteries and strictly controlling the iron-phosphorus ratio during the recycling process, high-purity amino acid-functionalized carbon-loaded ferrous phosphate suitable for battery-grade applications is prepared. The entire process employs low-energy reflux heating treatment and short-time high-temperature sintering, reducing energy consumption and ensuring the rational utilization of resources.

[0005] The specific technical solutions provided in this application are as follows: A method for regenerating ferrophosphide slag into carbon-coated ferrous phosphide is provided, the method comprising: S1. Pre-treat the ferrophosphate slag and then screen it to obtain ferrophosphate slag powder with a particle size of ≥200 mesh. S2. The phosphorus-iron slag powder is mixed with the first acid solution and heated to react. An iron source is added to the reacted material to obtain an iron-phosphorus mixture, and the iron-phosphorus ratio of the iron-phosphorus mixture is controlled to satisfy (1.75~2.1):1. S3. Prepare the iron-phosphorus mixture, dissolve it in a solvent with an amino acid salt and a carbon source, and react to obtain the ferrous phosphide precursor. S4. The ferrous phosphide precursor is heated in a reducing gas atmosphere to obtain carbon-coated ferrous phosphide.

[0006] In one specific embodiment, the pretreatment of the phosphorus-iron slag specifically includes: The ferrophosphorus slag is calcined at 700℃~900℃ for 2h~4h to remove organic matter and carbon powder to obtain the calcined product; the calcined product is mechanically crushed and passed through a 100-mesh sieve to obtain the sieved product; the sieved product is washed in a second acid solution and then washed with deionized water, and dried to obtain the pretreated ferrophosphorus slag; preferably, the second acid solution is a sulfuric acid solution, and the mass fraction of the sulfuric acid solution is 5wt%~10wt%.

[0007] In one specific embodiment, the solid-liquid ratio of the phosphorus iron slag powder to the first acid solution satisfies 1g:(15~60)mL; And / or, the first acid solution in S2 is a hydrochloric acid solution, and the concentration of the hydrochloric acid solution is 0.1 mol / L; And / or, the iron source includes one or more of ferrous oxalate, ferric oxalate, ferric chloride, ferrous sulfate, and ferric oxide.

[0008] In one specific embodiment, the heating reaction in S2 is carried out by water bath heating at a temperature of 50℃~100℃ with stirring, and the reaction time is 1h~10h. The mixture after the reaction is washed and dried to obtain the reacted substance.

[0009] In a specific embodiment, S3, preparing the iron-phosphorus mixture, dissolving the amino acid salt and carbon source in a solvent, and reacting them to obtain the ferrous phosphide precursor, specifically includes: The iron-phosphorus mixture, amino acid salt, and carbon source are dissolved in a solvent and stirred evenly, and then ultrasonically dispersed for 20-50 minutes to form a suspension. The suspension is then refluxed in an oil bath at 80-150°C for 6-24 hours. After the reaction is completed, the mixture is cooled to room temperature, and the cooled material is centrifuged, washed, and dried to obtain the ferrous phosphide precursor.

[0010] In one specific embodiment, the iron-phosphorus mixture, the amino acid salt, and the carbon source constitute a solid mixture, and the solid mixture is mixed and dissolved with the solvent at a solid-liquid mass ratio of 1:(10~100).

[0011] In one specific embodiment, the mass ratio of the iron-phosphorus mixture, the amino acid salt, and the carbon source satisfies 100:1:(10~100); And / or, the amino acid includes one or more of glycine, alanine, valine, leucine, proline, tryptophan, serine, and histidine; And / or, the carbon source includes one or more of glucose, sucrose, and chitosan.

[0012] In one specific embodiment, the solvent has a mass fraction of 5 wt% to 15 wt%. And / or, the solvent includes one or more of ethanol, water and methanol.

[0013] In a specific embodiment, S4, configuring the ferrous phosphide precursor to undergo a heating reaction under a reducing gas atmosphere to obtain carbon-coated ferrous phosphide, specifically includes: The ferrous phosphide precursor was heated to 500°C to 900°C at a rate of 1°C / min to 10°C / min under a continuous reducing gas atmosphere, and the temperature was maintained for 1h to 3h to carry out the reaction; the reacted material was then naturally cooled to room temperature to obtain the carbon-coated ferrous phosphide.

[0014] Corresponding to the above embodiments, a ferrous phosphide is provided, which is prepared by the method described above of regenerating ferrophosphide slag into carbon-coated ferrous phosphide.

[0015] Corresponding to the above embodiments, an application of ferrous phosphide as a raw material in the preparation of electrodes is provided.

[0016] The embodiments of this application have the following beneficial effects: The pretreated ferrophosphorus slag is screened to obtain ferrophosphorus slag powder with a particle size of ≥200 mesh. The ferrophosphorus slag powder is mixed with a first acid solution and heated to react. An iron source is added to the reactant to obtain an iron-phosphorus mixture, wherein the iron-phosphorus mixture is activated ferrophosphorus slag powder, and the iron-phosphorus ratio of the iron-phosphorus mixture is controlled to meet (1.75~2.1):1. The iron-phosphorus mixture is then dissolved in a solvent with amino acid salts and a carbon source to obtain a ferrous phosphide precursor. The ferrous phosphide precursor is an amino acid-functionalized carbon-layer supported ferrous phosphide precursor. The ferrous phosphide precursor is heated under a reducing gas atmosphere to obtain carbon-coated ferrous phosphide. This application obtains high-purity amino acid-functionalized carbon-layer supported ferrous phosphide that can be used in battery-grade applications by strictly controlling the iron-phosphorus ratio during the recycling process. At the same time, the entire process adopts low-energy reflux heating treatment and short-time high-temperature sintering, reducing energy consumption and ensuring the rational utilization of resources. Attached Figure Description

[0017] To more clearly illustrate the embodiments of this application, the accompanying drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0018] Figure 1 A schematic diagram showing a method for regenerating ferrophosphide slag into carbon-coated ferrous phosphide; Figure 2 The LSV curve of Example 1 is shown. Detailed Implementation

[0019] To make the objectives, technical solutions, and advantages of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0020] The "range" disclosed herein is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also expected. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0021] Unless otherwise specified in this application, all embodiments and preferred embodiments mentioned herein can be combined to form new technical solutions.

[0022] Unless otherwise specified, all technical features and preferred features mentioned herein can be combined to form new technical solutions.

[0023] In this application, unless otherwise specified, all steps mentioned herein may be performed sequentially or randomly, but are preferably performed sequentially. For example, if the method includes steps (a) and (b), it means that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, if the method may also include step (c), it means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein in the specification of this application is for the purpose of describing particular embodiments only and is not intended to be limiting of the application. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0025] This application provides a method for regenerating ferrophosphide slag into carbon-coated ferrous phosphide, such as... Figure 1 As shown, the method includes the following steps: S1. Pre-treat the ferrophosphate slag and then screen it to obtain ferrophosphate slag powder with a particle size of ≥200 mesh.

[0026] Phosphate residue originates from the residue of spent lithium iron phosphate battery cathode sheets after physical crushing, pyrolysis, and lithium extraction. Phosphate residue typically contains 10%–30% carbon. Pretreatment of the phosphate residue can remove organic matter and carbon. Specific pretreatment methods for phosphate residue include: The ferrophosphate slag was placed in a muffle furnace and calcined at 700℃~900℃ for 2h~4h to remove organic matter and carbon powder to obtain the calcined product. The calcined product was mechanically crushed and passed through a 100-mesh sieve to obtain the sieved product. The sieved product was washed in a second acid solution, which was sulfuric acid solution with a mass fraction of 5wt%~10wt%, to remove residual alkaline impurities. Finally, it was washed with deionized water until the filtrate was neutral and vacuum dried at 80℃~100℃ to constant weight. Then, it was screened to obtain ferrophosphate slag powder with a particle size of ≥200 mesh. XRD analysis showed that the main component of the pretreated ferrophosphate slag was FePO4, the iron-phosphorus molar ratio was about 0.95~1.05, and the total impurity content was ≤1wt%.

[0027] S2. Mix the phosphorus-iron slag powder with the first acid solution and heat it to react. Add an iron source to the reacted material to obtain an iron-phosphorus mixture, and control the iron-phosphorus ratio of the iron-phosphorus mixture to satisfy (1.75~2.1):1.

[0028] The above-mentioned iron-phosphorus slag powder was mixed with hydrochloric acid solution (concentration: 0.1 mol / L) and added to a beaker. The beaker was placed on a magnetic stirrer, and the reaction was heated in a water bath at 50℃~100℃ with stirring for 1h~10h. The mixture was washed and dried to obtain the reacted substance. After the reaction, the mixture was filtered using a vacuum filtration device. The filter residue was repeatedly washed with deionized water until the pH of the filtrate was within the range of 6~7. The pH of the filtrate was tested using pH test paper. The filter cake was placed in a petri dish and dried in a vacuum drying oven at 70℃ for 12 hours to obtain the dried powder. The iron-phosphorus ratio of the powder was tested using ICP. Then, an iron source was added and mixed evenly, controlling the iron-phosphorus ratio of the mixed iron-phosphorus mixture to be (1.75~2.1):1.

[0029] The solid-liquid ratio of the ferrophosphorus slag powder to the first acid solution is 1g:(15~60)mL. Specifically, the solid-liquid ratio of the ferrophosphorus slag powder to the first acid solution is 1g:15mL, 1g:20mL, 1g:25mL, 1g:30mL, 1g:35mL, 1g:40mL, 1g:45mL, 1g:50mL, 1g:55mL, 1g:60mL, or any combination of two of the above values. By setting the above ratio, it is ensured that the ferrophosphorus slag powder and dilute hydrochloric acid are mixed in the above proportion to achieve a complete reaction.

[0030] Specifically, the iron source includes, but is not limited to, one or more of ferrous oxalate, ferric oxalate, ferric chloride, ferrous sulfate, and ferric oxide. The iron-phosphorus mixture is tested to obtain the iron-phosphorus ratio, specifically, the iron-phosphorus ratio in the mixture must satisfy 1.75:1, 1.8:1, 1.95:1, 2:1, 2.05:1, 2.1:1, or a range consisting of any two of the above values.

[0031] S3. Prepare an iron-phosphorus mixture, dissolve it in a solvent with an amino acid salt and a carbon source, and react to obtain an iron phosphide precursor.

[0032] Specifically, the iron-phosphorus mixture, amino acid salt, and carbon source are dissolved in a solvent and placed in a beaker and stirred evenly. Then, ultrasonic dispersion is performed for 20 to 50 minutes to form a suspension, which is a black suspension. The suspension is transferred to a flask and heated in an oil bath at 80°C to 150°C for 6 to 24 hours under reflux. After the reaction is completed, the mixture is naturally cooled to room temperature. The cooled material is then centrifuged, washed, and dried to obtain the ferrous phosphide precursor.

[0033] Furthermore, the iron-phosphorus mixture, amino acid salt, and carbon source constitute a solid mixture, which is then mixed and dissolved with the solvent at a solid-liquid mass ratio of 1:(10~100). Specifically, the solid-liquid mass ratio of the solid mixture to the solvent satisfies 1:10, 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90, 1:100, or any two of the above values.

[0034] The mass ratio of the iron-phosphorus mixture, amino acid salt, and carbon source satisfies 100:1:(10~100). Specifically, the mass ratio of the iron-phosphorus mixture, amino acid salt, and carbon source satisfies 100:1:10, 100:1:20, 100:1:30, 100:1:40, 100:1:50, 100:1:60, 100:1:70, 100:1:80, 100:1:90, 100:1:100, or a range consisting of any two of the above values.

[0035] It should be noted that the amino acids in this embodiment include, but are not limited to, one or more of glycine, alanine, valine, leucine, proline, tryptophan, serine, and histidine, and the carbon sources include, but are not limited to, one or more of glucose, sucrose, and chitosan.

[0036] The solvent is selected from one or more of ethanol, water and methanol, and the mass fraction of the solvent is 5wt% to 15wt%. Specifically, the mass fraction of the solvent is 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, or any range of two of the above values.

[0037] S4. Prepare ferrous phosphide precursor and react it under a reducing gas atmosphere to obtain carbon-coated ferrous phosphide.

[0038] Ferrous phosphide precursor powder was subjected to a reaction under continuous Ar / H2 purging, with the temperature increased from room temperature to 500℃~900℃ at a rate of 1℃ / min~10℃ / min and held constant for 1h~3h. After cooling to room temperature, the black powder was collected, which is the final product carbon-coated ferrous phosphide.

[0039] Corresponding to the above embodiments, a ferrous phosphide is provided, which is prepared by the above method of regenerating ferric phosphide slag into carbon-coated ferrous phosphide.

[0040] Corresponding to the above embodiments, an application of ferrous phosphide as a raw material in the preparation of electrodes is provided.

[0041] Example 1 Corresponding to the above embodiments, this embodiment provides a method for regenerating ferrophosphide slag into carbon-coated ferrous phosphide, including the following steps: Step 1.1: Weigh 20g of phosphorus iron slag powder that has passed through a 200-mesh sieve and place it in a 100mL beaker; Step 1.2: Add the above mixture to a 0.1M HCl solution, with a liquid-to-solid ratio of 30:1 (mL / g). Step 1.3: Place the beaker on a magnetic stirrer and stir at high speed for 3 hours under a 60°C water bath heating condition; Step 1.4 After the reaction is complete, filter the solution using a vacuum filtration device. Wash the filter residue with deionized water five times until the pH value of the filtrate reaches 6.5 (tested with pH test paper). Step 1.5: Place the final filter cake into a petri dish and dry it in a vacuum drying oven at 70°C for 12 hours to obtain a dried powder; Step 1.6: The iron-to-phosphorus ratio of the powder was tested to be 0.98; Step 1.7: Test results show that 23.87g of ferrous oxalate dihydrate was added to the powder and mixed evenly to make the iron-to-phosphorus ratio 2:1. Step 2: Preparation of carbon-coated Fe2P precursor: Step 2.1: Weigh 10g of activated phosphorus iron slag powder, 0.1g of lysine salt, and 4g of glucose; Step 2.2: Add 200 mL of 10% ethanol; Step 2.3: Stir well in a beaker and ultrasonically disperse for 30 minutes to form a uniform black suspension; Step 2.4: Completely transfer the suspension to a 500mL three-necked flask; Step 2.5: Under oil bath heating at 120°C, reflux for 12 hours, and allow to cool naturally to room temperature after the reaction time is complete. Step 2.6: Obtain the precursor powder by centrifugation and washing; Step 2.7: Dry the precursor powder in a forced-air drying oven at 80°C for 6 hours.

[0042] Step 3: Prepare a carbon-coated Fe2P layer: Step 3.1: Under the condition of continuous Ar / H2 gas flow (flow rate of 150 mL / min), the dried powder is heated from room temperature to 750℃ at a heating rate of 5℃ / min and held at the temperature for 2 hours. Step 3.2: After the temperature drops to room temperature, allow it to cool naturally to room temperature. Step 3.3: Collect the black final product, carbon-coated ferrous phosphide.

[0043] Example 2 Step 1.1: Weigh 20 g of phosphorus iron slag powder that has passed through a 200-mesh sieve and place it in a 100 mL beaker; Step 1.2: Add the above mixture to a 0.1M HCl solution, with a liquid-to-solid ratio of 30:1 (mL / g). Step 1.3: Place the beaker on a magnetic stirrer and stir at high speed for 3 hours under a 60°C water bath heating condition; Step 1.4 After the reaction is complete, filter the solution using a vacuum filtration device. Wash the filter residue with deionized water five times until the pH value of the filtrate reaches 6.5 (tested with pH test paper). Step 1.5: Place the final filter cake into a petri dish and dry it in a vacuum drying oven at 70°C for 12 hours to obtain a dried powder; Step 1.6: The iron-to-phosphorus ratio of the powder was tested to be 0.98; Step 1.7: Add 18.02g of ferrous oxalate dihydrate to the powder and mix well to make the iron-to-phosphorus ratio 1.75:1. Step 2: Preparation of carbon-coated Fe2P precursor: Step 2.1: Weigh 10g of activated phosphorus iron slag powder, 0.1g of lysine salt, and 4g of glucose; Step 2.2: Add 200 mL of 10% ethanol; Step 2.3: Stir well in a beaker and ultrasonically disperse for 30 minutes to form a uniform black suspension; Step 2.4: Completely transfer the suspension to a 500mL three-necked flask; Step 2.5: Under oil bath heating at 120°C, reflux for 12 hours, and allow to cool naturally to room temperature after the reaction time is complete. Step 2.6: Obtain the precursor powder by centrifugation and washing; Step 2.7: Dry the precursor powder in a forced-air drying oven at 80°C for 6 hours.

[0044] Step 3: Prepare a carbon-coated Fe2P layer: Step 3.1: Under the condition of continuous Ar / H2 flow (flow rate of 150 mL / min), the dried powder is heated from room temperature to 750℃ at a heating rate of 5℃ / min and held at the temperature for 2 hours. Step 3.2: After the temperature drops to room temperature, allow it to cool naturally to room temperature. Step 3.3: Collect the black final product, carbon-coated ferrous phosphide.

[0045] Example 3 Step 1.1: Weigh 20 g of phosphorus iron slag powder that has passed through a 200-mesh sieve and place it in a 100 mL beaker; Step 1.2: Add the above mixture to a 0.1M HCl solution, with a liquid-to-solid ratio of 30:1 (mL / g). Step 1.3: Place the beaker on a magnetic stirrer and stir at high speed for 3 hours under a 60°C water bath heating condition; Step 1.4 After the reaction is complete, filter the solution using a vacuum filtration device. Wash the filter residue with deionized water five times until the pH value of the filtrate reaches 6.5 (tested with pH test paper). Step 1.5: Place the final filter cake into a petri dish and dry it in a vacuum drying oven at 70°C for 12 hours to obtain a dried powder; Step 1.6: The iron-to-phosphorus ratio of the powder was tested to be 0.98; Step 1.7: Add 19.20g of ferrous oxalate dihydrate to the powder and mix well to make the iron-to-phosphorus ratio 1.8:1. Step 2: Preparation of carbon-coated Fe2P precursor: Step 2.1: Weigh 10g of activated phosphorus iron slag powder, 0.1g of lysine salt, and 4g of glucose; Step 2.2: Add 200 mL of 10% ethanol; Step 2.3: Stir well in a beaker and ultrasonically disperse for 30 minutes to form a uniform black suspension; Step 2.4: Completely transfer the suspension to a 500mL three-necked flask; Step 2.5: Under oil bath heating at 120°C, reflux for 12 hours, and allow to cool naturally to room temperature after the reaction time is complete. Step 2.6: Obtain the precursor powder by centrifugation and washing; Step 2.7: Dry the precursor powder in a forced-air drying oven at 80°C for 6 hours.

[0046] Step 3: Prepare a carbon-coated Fe2P layer: Step 3.1: Under the condition of continuous Ar / H2 flow (flow rate of 150 mL / min), the dried powder is heated from room temperature to 750℃ at a heating rate of 5℃ / min and held at the temperature for 2 hours. Step 3.2: After the temperature drops to room temperature, allow it to cool naturally to room temperature. Step 3.3: Collect the black final product, carbon-coated ferrous phosphide.

[0047] Example 4 Step 1.1: Weigh 20 g of phosphorus iron slag powder that has passed through a 200-mesh sieve and place it in a 100 mL beaker; Step 1.2: Add the above mixture to a 0.1M HCl solution, with a liquid-to-solid ratio of 30:1 (mL / g). Step 1.3: Place the beaker on a magnetic stirrer and stir at high speed for 3 hours under a 60°C water bath heating condition; Step 1.4 After the reaction is complete, filter the solution using a vacuum filtration device. Wash the filter residue with deionized water five times until the pH value of the filtrate reaches 6.5 (tested with pH test paper). Step 1.5: Place the final filter cake into a petri dish and dry it in a vacuum drying oven at 70°C for 12 hours to obtain a dried powder; Step 1.6: The iron-to-phosphorus ratio of the powder was tested to be 0.98; Step 1.7: Add 21.53 g of ferrous oxalate dihydrate to the powder and mix well to achieve an iron-to-phosphorus ratio of 1.9:1. Step 2: Preparation of carbon-coated Fe2P precursor: Step 2.1: Weigh 10g of activated phosphorus iron slag powder, 0.1g of lysine salt, and 4g of glucose; Step 2.2: Add 200 mL of 10% ethanol; Step 2.3: Stir well in a beaker and ultrasonically disperse for 30 minutes to form a uniform black suspension; Step 2.4: Completely transfer the suspension to a 500mL three-necked flask; Step 2.5: Under oil bath heating at 120°C, reflux for 12 hours, and allow to cool naturally to room temperature after the reaction time is complete. Step 2.6: Obtain the precursor powder by centrifugation and washing; Step 2.7: Dry the precursor powder in a forced-air drying oven at 80°C for 6 hours.

[0048] Step 3: Prepare a carbon-coated Fe2P layer: Step 3.1: Under the condition of continuous Ar / H2 flow (flow rate of 150 mL / min), the dried powder is heated from room temperature to 750℃ at a heating rate of 5℃ / min and held at the temperature for 2 hours. Step 3.2: After the temperature drops to room temperature, allow it to cool naturally to room temperature. Step 3.3: Collect the black final product, carbon-coated ferrous phosphide.

[0049] Example 5 Step 1.1: Weigh 20g of phosphorus iron slag powder that has passed through a 200-mesh sieve and place it in a 100mL beaker; Step 1.2: Add the above mixture to a 0.1M HCl solution, with a liquid-to-solid ratio of 30:1 (mL / g). Step 1.3: Place the beaker on a magnetic stirrer and stir at high speed for 3 hours under a 60°C water bath heating condition; Step 1.4 After the reaction is complete, filter the solution using a vacuum filtration device. Wash the filter residue with deionized water five times until the pH value of the filtrate reaches 6.5 (tested with pH test paper). Step 1.5: Place the final filter cake into a petri dish and dry it in a vacuum drying oven at 70°C for 12 hours to obtain a dried powder; Step 1.6: The iron-to-phosphorus ratio of the powder was tested to be 0.98; Step 1.7: Test results show that 26.21g of ferrous oxalate dihydrate was added to the powder and mixed evenly to make the iron-to-phosphorus ratio 2.1:1. Step 2: Preparation of carbon-coated Fe2P precursor: Step 2.1: Weigh 10g of activated phosphorus iron slag powder, 0.1g of lysine salt, and 4g of glucose; Step 2.2: Add 200 mL of 10% ethanol; Step 2.3: Stir well in a beaker and ultrasonically disperse for 30 minutes to form a uniform black suspension; Step 2.4: Completely transfer the suspension to a 500mL three-necked flask; Step 2.5: Under oil bath heating at 120°C, reflux for 12 hours, and allow to cool naturally to room temperature after the reaction time is complete. Step 2.6: Obtain the precursor powder by centrifugation and washing; Step 2.7: Dry the precursor powder in a forced-air drying oven at 80°C for 6 hours.

[0050] Step 3: Prepare a carbon-coated Fe2P layer: Step 3.1: Under the condition of continuous Ar / H2 flow (flow rate of 150 mL / min), the dried powder is heated from room temperature to 750℃ at a heating rate of 5℃ / min and held at the temperature for 2 hours. Step 3.2: After the temperature drops to room temperature, allow it to cool naturally to room temperature. Step 3.3: Collect the black final product, carbon-coated ferrous phosphide.

[0051] Example 6 Step 1.1: Weigh 20g of phosphorus iron slag powder that has passed through a 200-mesh sieve and place it in a 100mL beaker; Step 1.2: Add the above mixture to a 0.1M HCl solution, with a liquid-to-solid ratio of 30:1 (mL / g). Step 1.3: Place the beaker on a magnetic stirrer and stir at high speed for 3 hours under a 60°C water bath heating condition; Step 1.4 After the reaction is complete, filter the solution using a vacuum filtration device. Wash the filter residue with deionized water five times until the pH value of the filtrate reaches 6.5 (tested with pH test paper). Step 1.5: Place the final filter cake into a petri dish and dry it in a vacuum drying oven at 70°C for 12 hours to obtain a dried powder; Step 1.6: The iron-to-phosphorus ratio of the powder was tested to be 0.98; Step 1.7: Add 12.16g of ferrous oxalate dihydrate (FeC2O42H2O) to the powder and mix well to make the iron-to-phosphorus ratio 1.5:1. Step 2: Preparation of carbon-coated Fe2P precursor: Step 2.1: Weigh 10g of activated phosphorus iron slag powder, 0.1g of lysine salt, and 4g of glucose; Step 2.2: Add 200 mL of 10% ethanol; Step 2.3: Stir well in a beaker and ultrasonically disperse for 30 minutes to form a uniform black suspension; Step 2.4: Completely transfer the suspension to a 500mL three-necked flask; Step 2.5: Under oil bath heating at 120°C, reflux for 12 hours, and allow to cool naturally to room temperature after the reaction time is complete. Step 2.6: Obtain the precursor powder by centrifugation and washing; Step 2.7: Dry the precursor powder in a forced-air drying oven at 80°C for 6 hours.

[0052] Step 3: Prepare a carbon-coated Fe2P layer: Step 3.1: Under the condition of continuous Ar / H2 flow (flow rate of 150 mL / min), the dried powder is heated from room temperature to 750℃ at a heating rate of 5℃ / min and held at the temperature for 2 hours. Step 3.2: After the temperature drops to room temperature, allow it to cool naturally to room temperature. Step 3.3: Collect the black final product, carbon-coated ferrous phosphide.

[0053] Example 7 Corresponding to the above embodiments, the only difference between this embodiment 7 and embodiment 1 is that the ratio of iron phosphorus, amino acid salt and carbon source in this embodiment is 10:0.1:5, and the rest is the same as in embodiment 1.

[0054] Example 8 Corresponding to the above embodiments, the only difference between this embodiment 8 and embodiment 1 is that the ratio of iron phosphorus, amino acid salt and carbon source in this embodiment is 10:0.1:1, and the rest is the same as in embodiment 1.

[0055] Example 9 Corresponding to the above embodiments, the only difference between this embodiment 9 and embodiment 1 is that the ratio of iron phosphorus, amino acid salt and carbon source in this embodiment is 10:0.1:10, and the rest is the same as in embodiment 1.

[0056] Comparative Example 1 Step 1.1: Weigh 20g of phosphorus iron slag powder that has passed through a 200-mesh sieve and place it in a 100mL beaker; Step 1.2: Add the above mixture to a 0.1M HCl solution, with a liquid-to-solid ratio of 30:1 (mL / g). Step 1.3: Place the beaker on a magnetic stirrer and stir at high speed for 3 hours under a 60°C water bath heating condition; Step 1.4 After the reaction is complete, filter the solution using a vacuum filtration device. Wash the filter residue with deionized water five times until the pH value of the filtrate reaches 6.5 (tested with pH test paper). Step 1.5: Place the final filter cake into a petri dish and dry it in a vacuum drying oven at 70°C for 12 hours to obtain a dried powder; Step 1.6: The iron-to-phosphorus ratio of the powder was tested to be 0.98; Step 1.7: Test results show that 23.87 g of ferrous oxalate dihydrate was added to the powder and mixed evenly to make the iron-to-phosphorus ratio 2:1. Step 2: Preparation of carbon-coated Fe2P precursor: Step 2.1: Weigh 10g of activated phosphorus iron slag powder and 4g of glucose; Step 2.2: Add 200 mL of 10% ethanol; Step 2.3: Stir well in a beaker and ultrasonically disperse for 30 minutes to form a uniform black suspension; Step 2.4: Completely transfer the suspension to a 500mL three-necked flask; Step 2.5: Under oil bath heating at 120°C, reflux for 12 hours, and allow to cool naturally to room temperature after the reaction time is complete. Step 2.6: Obtain the precursor powder by centrifugation and washing; Step 2.7: Dry the precursor powder in a forced-air drying oven at 80°C for 6 hours.

[0057] Step 3: Prepare a carbon-coated Fe2P layer: Step 3.1: Under the condition of continuous Ar / H2 gas flow (flow rate of 150 mL / min), the dried powder is heated from room temperature to 750℃ at a heating rate of 5℃ / min and held at the temperature for 2 hours. Step 3.2: After the temperature drops to room temperature, allow it to cool naturally to room temperature. Step 3.3: Collect the black final product, carbon-coated ferrous phosphide.

[0058] Comparative Example 2 Step 1.1: Weigh 20 g of phosphorus iron slag powder that has passed through a 200-mesh sieve and place it in a 100 mL beaker; Step 1.2: Add the above mixture to a 0.1M HCl solution, with a liquid-to-solid ratio of 30:1 (mL / g). Step 1.3: Place the beaker on a magnetic stirrer and stir at high speed for 3 hours under a 60°C water bath heating condition; Step 1.4 After the reaction is complete, filter the solution using a vacuum filtration device. Wash the filter residue with deionized water five times until the pH value of the filtrate reaches 6.5 (tested with pH test paper). Step 1.5: Place the final filter cake into a petri dish and dry it in a vacuum drying oven at 70°C for 12 hours to obtain a dried powder; Step 1.6: The iron-to-phosphorus ratio of the powder was tested to be 0.98; Step 1.7: Test results show that 23.87g of ferrous oxalate dihydrate was added to the powder and mixed evenly to make the iron-to-phosphorus ratio 2:1. Step 2: Preparation of carbon-coated Fe2P precursor: Step 2.1: Weigh 10g of activated ferrophosphorus slag powder and 0.1g of lysine salt; Step 2.2: Add 200 mL of 10% ethanol; Step 2.3: Stir well in a beaker and ultrasonically disperse for 30 minutes to form a uniform black suspension; Step 2.4: Completely transfer the suspension to a 500mL three-necked flask; Step 2.5: Under oil bath heating at 120°C, reflux for 12 hours, and allow to cool naturally to room temperature after the reaction time is complete. Step 2.6: Obtain the precursor powder by centrifugation and washing; Step 2.7: Dry the precursor powder in a forced-air drying oven at 80°C for 6 hours.

[0059] Step 3: Prepare a carbon-coated Fe2P layer: Step 3.1: Under the condition of continuous Ar / H2 gas flow (flow rate of 150 mL / min), the dried powder is heated from room temperature to 750℃ at a heating rate of 5℃ / min and held at the temperature for 2 hours. Step 3.2: After the temperature drops to room temperature, allow it to cool naturally to room temperature. Step 3.3: Collect the black final product, carbon-coated ferrous phosphide.

[0060] Comparative Example 3 Corresponding to the above embodiments, the only difference between this comparative example and Example 1 is that the ratio of iron phosphorus, amino acid salt, and carbon source in this comparative example is 10:0.1:15, and the rest is the same as Example 1.

[0061] Comparative Example 4 Corresponding to the above embodiments, the only difference between this comparative example and Example 1 is that the ratio of iron phosphorus, amino acid salt, and carbon source in this comparative example is 10:0.1:0.5, and the rest is the same as Example 1.

[0062] Comparative Example 5 Step 1.1: Weigh 20g of phosphorus iron slag powder that has passed through a 200-mesh sieve and place it in a 100mL beaker; Step 1.2: Add the above mixture to a 0.1M HCl solution, with a liquid-to-solid ratio of 30:1 (mL / g). Step 1.3: Place the beaker on a magnetic stirrer and stir at high speed for 3 hours under a 60°C water bath heating condition; Step 1.4 After the reaction is complete, filter the solution using a vacuum filtration device. Wash the filter residue with deionized water five times until the pH value of the filtrate reaches 6.5 (tested with pH test paper). Step 1.5: Place the final filter cake into a petri dish and dry it in a vacuum drying oven at 70°C for 12 hours to obtain a dried powder; Step 1.6: The iron-to-phosphorus ratio of the powder was tested to be 0.98; Step 1.7: Test results show that 35.58 g of ferrous oxalate dihydrate was added to the powder and mixed evenly to make the iron-to-phosphorus ratio 2.5:1. Step 2: Preparation of carbon-coated Fe2P precursor: Step 2.1: Weigh 10g of activated phosphorus iron slag powder, 0.1g of lysine salt, and 4g of glucose; Step 2.2: Add 200 mL of 10% ethanol; Step 2.3: Stir well in a beaker and ultrasonically disperse for 30 minutes to form a uniform black suspension; Step 2.4: Completely transfer the suspension to a 500mL three-necked flask; Step 2.5: Under oil bath heating at 120°C, reflux for 12 hours, and allow to cool naturally to room temperature after the reaction time is complete. Step 2.6: Obtain the precursor powder by centrifugation and washing; Step 2.7: Dry the precursor powder in a forced-air drying oven at 80°C for 6 hours.

[0063] Step 3: Prepare a carbon-coated Fe2P layer: Step 3.1: Under the condition of continuous Ar / H2 flow (flow rate of 150 mL / min), the dried powder is heated from room temperature to 750℃ at a heating rate of 5℃ / min and held at the temperature for 2 hours. Step 3.2: After the temperature drops to room temperature, allow it to cool naturally to room temperature. Step 3.3: Collect the black final product, carbon-coated ferrous phosphide.

[0064] Preparation of the working electrode: The ferrous phosphide powder prepared in the above examples and comparative examples was mixed evenly with isopropanol and Nafion (the weight ratio of electrocatalyst powder to Nafion was 9:1) to prepare a mixed slurry. This slurry was then drop-coated onto a glassy carbon electrode and dried at room temperature to obtain the working electrode. Nafion is a perfluorosulfonic acid polymer composed of a perfluorocarbon backbone and sulfonic acid groups, belonging to artificially synthesized ion-exchange polymers.

[0065] The working electrodes prepared in the above embodiments were subjected to OER testing, and the test results are shown in Table 1. OER testing: LSV testing was performed in 1 M KOH solution under the following conditions: 0~0.7 V vs. Ag / AgCl, scan rate of 5 mV / s. -1 The rotational speed was 1600 rpm; the stability test was conducted using the chronovoltammetry method with a current density of 10 mA / cm². -2 Overpotential is defined as the portion of the actual voltage required to reach a specific current density that exceeds the theoretical voltage by 1.23V (vs. RHE), η=E 实际 -E 理论 =E 实际 1.23V (vs. RHE). Here, overpotential @50 indicates a current density of 50 mA / cm². 2 Overpotential at that time.

[0066] Table 1 Test results for each set of embodiments

[0067] Combining Table 1 and Figure 2 The test results clearly show that the overpotential of the synthesized carbon-coated ferrous phosphide is 50 mA cm⁻¹. -2 At a current density of only 309 mV, the Tafel slope is 81 mVdec. Compared to traditional ferrophosphate slag regeneration processes, we transform it into a high-value product applicable as an electrode. Compared to traditional methods of regenerating ferrophosphate, this invention employs low-energy reflux heating treatment and short-time high-temperature sintering, reducing energy consumption and shortening the synthesis process. Figure 2 As can be seen from the LSV curve in Example 1, at a current density of 50 mA / cm², -2In this case, the corresponding potential is 1.546V (vsRHE), and the overpotential is only 309mV, which means that when the electrode is undergoing a charge-discharge reaction, the internal kinetic resistance is extremely small and the charge transfer is very rapid; at the same time, the low overpotential helps to reduce stress concentration inside the electrode, so as to ensure the smoothness of the reaction.

[0068] Based on Examples 1-6 and Comparative Example 5, it is clear that during the reaction process, by adding different amounts of ferrous oxalate dihydrate to the powder to achieve different iron-to-phosphorus ratios, when the iron-to-phosphorus ratio is within the range of (1.75~2.1):1, the overpotential of the synthesized carbon-coated ferrous phosphide electrode is maintained at 50 mA / cm². -2 The current density is maintained below 356mV. However, when the iron-phosphorus ratio exceeds the above range, i.e. when the iron-phosphorus ratio is configured as 1.5:1, the overpotential reaches 396mV, which leads to a reduction in the battery's initial charging capacity and a significant decrease in the actual usable capacity. This severely reduces the specific capacity and initial coulombic efficiency of the entire battery. Furthermore, an excessively high overpotential means that charge transport inside the electrodes is hindered, which will lead to a significant increase in the battery's internal resistance and a sharp decline in the battery's rate performance and cycle life.

[0069] Based on Examples 7-9 and Comparative Examples 3-4, it is clear that when the amounts of iron phosphorus, amino acid salt, and carbon source in the reactants are selected in different proportions, and when the proportions of iron phosphorus, amino acid salt, and carbon source meet the scope of this application, the resulting overpotential is significantly lower than the test results when the proportions of iron phosphorus, amino acid salt, and carbon source exceed the scope of this application. This further confirms that the carbon-coated ferrous phosphide prepared using the scheme in this example has extremely low internal kinetic resistance and very rapid charge transfer during the charge-discharge reaction. At the same time, the low overpotential helps to reduce stress concentration inside the electrode, thereby ensuring the smoothness of the reaction.

[0070] Combining Comparative Examples 1 and 2, it can be concluded that no amino acid salt was added for activation in Comparative Example 1, and no carbon source was added in Comparative Example 2, so the carbon content was 0. Combining Examples 1 and 2, it can be seen that within a certain range of iron-phosphorus ratio, when mixed with amino acid salt and carbon source, they can work together to achieve a dynamic equilibrium between iron and phosphorus during the reaction process, thereby forming an amino acid-functionalized carbon layer-loaded ferrous phosphide precursor. However, when amino acid salt or carbon source is lacking, the overpotential value of the prepared ferrous phosphide is as high as 457mV, requiring a larger additional voltage to be applied at the same current density, resulting in poor energy efficiency.

[0071] Although preferred embodiments have been described in this application, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of the embodiments of this application.

[0072] Obviously, those skilled in the art can make various modifications and variations to this application without departing from the spirit and scope of this application. Therefore, if such modifications and variations fall within the scope of the claims of this application and their equivalents, this application also intends to include such modifications and variations.

Claims

1. A method for regenerating ferrophosphide slag into carbon-coated ferrous phosphide, characterized in that, The method includes: S1. Pre-treat the ferrophosphate slag and then screen it to obtain ferrophosphate slag powder with a particle size of ≥200 mesh. S2. The phosphorus-iron slag powder is mixed with the first acid solution and heated to react. An iron source is added to the reacted material to obtain an iron-phosphorus mixture, and the iron-phosphorus ratio of the iron-phosphorus mixture is controlled to satisfy (1.75~2.1):

1. S3. Prepare the iron-phosphorus mixture, dissolve it in a solvent with an amino acid salt and a carbon source, and react to obtain the ferrous phosphide precursor. S4. The ferrous phosphide precursor is heated in a reducing gas atmosphere to obtain carbon-coated ferrous phosphide.

2. The method for regenerating ferrophosphide slag into carbon-coated ferrous phosphide according to claim 1, characterized in that, The pretreatment of the phosphorus-iron slag specifically includes: The phosphorus-iron slag was calcined at 700℃~900℃ for 2h~4h to remove organic matter and carbon powder to obtain the calcined product; The calcined product is mechanically crushed and passed through a 100-mesh sieve to obtain the sieved product; The sieved product was washed with a second acid solution and then with deionized water. After washing, it was dried to obtain pretreated phosphorus iron slag. Preferably, the second acid solution is a sulfuric acid solution, and the mass fraction of the sulfuric acid solution is 5wt%~10wt%.

3. The method for regenerating ferrophosphide slag into carbon-coated ferrous phosphide according to claim 1 or 2, characterized in that, The solid-liquid ratio of the phosphorus iron slag powder to the first acid solution is 1g:(15~60)mL; And / or, the first acid solution in S2 is a hydrochloric acid solution, and the concentration of the hydrochloric acid solution is 0.1 mol / L; And / or, the iron source includes one or more of ferrous oxalate, ferric oxalate, ferric chloride, ferrous sulfate and ferric oxide; And / or, the heating reaction in S2 is carried out by water bath heating at a temperature of 50℃~100℃ with stirring, and the reaction time is 1h~10h. The mixture after the reaction is washed and dried to obtain the reaction substance.

4. The method for regenerating ferrophosphide slag into carbon-coated ferrous phosphide according to claim 1 or 2, characterized in that, S3. Prepare the iron-phosphorus mixture, dissolve it in a solvent with an amino acid salt and a carbon source, and react to obtain the ferrous phosphide precursor, specifically including: The iron-phosphorus mixture, amino acid salt, and carbon source are dissolved in a solvent and stirred evenly, and then ultrasonically dispersed for 20 to 50 minutes to form a suspension. The suspension was prepared and refluxed in an oil bath at a temperature of 80°C to 150°C for 6 to 24 hours. After the reaction was completed, the mixture was cooled to room temperature, and the cooled material was centrifuged, washed, and dried to obtain the ferrous phosphide precursor.

5. The method for regenerating ferrophosphide slag into carbon-coated ferrous phosphide according to claim 4, characterized in that, The iron-phosphorus mixture, the amino acid salt, and the carbon source constitute a solid mixture, and the solid mixture is mixed and dissolved with the solvent at a solid-liquid mass ratio of 1:(10~100).

6. The method for regenerating ferrophosphide slag into carbon-coated ferrous phosphide according to claim 4, characterized in that, The mass ratio of the iron-phosphorus mixture, the amino acid salt, and the carbon source satisfies 100:1:(10~100); And / or, the amino acid includes one or more of glycine, alanine, valine, leucine, proline, tryptophan, serine, and histidine; And / or, the carbon source includes one or more of glucose, sucrose, and chitosan.

7. The method for regenerating ferrophosphide slag into carbon-coated ferrous phosphide according to claim 4, characterized in that, The solvent has a mass fraction of 5wt% to 15wt%. And / or, the solvent is selected from one or more of ethanol, water and methanol.

8. The method for regenerating ferrophosphide slag into carbon-coated ferrous phosphide according to claim 1 or 2, characterized in that, S4. The ferrous phosphide precursor is heated under a reducing gas atmosphere to obtain carbon-coated ferrous phosphide, specifically including: The ferrous phosphide precursor was heated to 500°C to 900°C at a rate of 1°C / min to 10°C / min under a continuous reducing gas atmosphere, and the temperature was maintained for 1h to 3h to carry out the reaction. The reacted material was naturally cooled to room temperature to obtain the carbon-coated ferrous phosphide.

9. A ferrous phosphide, characterized in that, The ferrous phosphide is prepared by the method described in any one of claims 1 to 8, which regenerates ferrophosphide slag into carbon-coated ferrous phosphide.

10. The use of ferrous phosphide as a raw material according to claim 9 in the preparation of electrodes.